Embree and Cairns on Phenomenology and Psychology - Barber, Michael (Investigaciones Fenomenológicas, 2021)
This article compares and contrasts Dorion Cairn’s treatment of the relationship between phenomenology and psychology with Embree’s handling of that same topic. Embree, who to a great degree aligns with Schutz, and Cairns converge on the treatment of behaviorism. However, fundamental differences appear in their contrasting approaches to psychology, with Cairns seeking to uphold the distinctiveness of philosophy/phenomenology over against psychology and Embree/Schutz inclining toward a more collaborative engagement with psychology. Their differences reflect their preference for transcendental philosophy or phenomenological psychology, both of which possible preferences were clearly recognized by Edmund Husserl in his “Nachwort zu meinen Ideen”. These preferences in turn have to do with the ultimate philosophical purposes each author is pursuing. Este artículo compara y contrasta el tratamiento de Dorion Cairn de la relación entre fenomenología y psicología con el manejo por parte de Embree del mismo tema. Embree —que en gran medida se alinea con Schutz— y Cairns convergen en el tratamiento del conductismo. Sin embargo, las diferencias fundamentales aparecen en sus enfoques que contrastan con la psicología, con Cairns tratando de mantener el carácter distintivo de la filosofía / fenomenología frente a la psicología y con Embree/Schutz inclinándose hacia un compromiso más colaborativo con la psicología. Sus diferencias reflejan sus preferencias por la filosofía trascendental o por la psicología fenomenológica —ambas preferencias posibles fueron claramente reconocidas por Edmund Husserl en su "Nachwort zu meinen Ideen". Estas preferencias a su vez tienen que ver con los propósitos filosóficos finales que persigue cada autor.